Aplikasi Teknologi Drone Sebagai Pelengkap Data Survei Lapang Untuk Pemetaan Ekosistem Terumbu Karang Menggunakan Citra Worldview-2 - Sugara, Ayub; Suryanita, Amelia; Maulana, Alfiqi; Anggoro, Ari; Siregar, Vincentius P. (Journal of Marine and Aquatic Sciences; Vol 8 No 2 (2022)DO - 10.24843/jmas.2022.v08.i02.p05, 2022)
Coral reefs are one of the important ecosystems that need data inventory in order to manage marine resources both spatially and temporally. Remote sensing with drone technology is one of the vehicles for collecting data related to coral reef ecosystems in real time. Along with the times, drones are widely used in research both in terrestrial and in coastal areas. This research was conducted on December 4 – 10, 2018 in the Karang Lebar, Seribu Islands, Jakarta. The purpose of this research was to explored the ability of drones as a vehicle to complement field survey data for coral reef mapping. In addition, conducting a pixel-based analysis for coral reef classification based on WorldView-2 satellite imagery using field survey data and additional data from drone data. Based on the results of the study, information was obtained that drone imagery can help visual interpretation in detecting coral reefs. Thus, field survey data that are not covered in the research area can be assisted by the use of drones as a complementary vehicle for field survey data. The coral reef classification process using WorldView-2 imagery can be mapped well. Drone imagery has proven to be an alternative in field data collection as a training area in identifying coral reef objects, such as with massive coral lifeforms that can be clearly seen from drone images. It's just that visual interpretation is limited because of the water column, making it difficult to identify objects.